Proceedings of the 3rd International Conference on Fun and Games 2010
DOI: 10.1145/1823818.1823825
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing self in puppet controlled virtual avatars

Abstract: Recent work in neuroscience suggests that there is a common coding in the brain between perception, imagination and execution of movement. Further, this common coding is considered to allow people to recognize their own movements when presented as abstract representations, and coordinate with these movements better. We are investigating how this 'own movement effect' could be extended to improve the interaction between players and game avatars, and how it might be leveraged to augment players' cognition. To ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…According to the previous studies [33][34][35], through the feedback of their own movement, visual observation or the feedback of avatar's (3D virtual character's) motion [36], humans can recognize and coordinate their movements better. The motion control module is the core of the system, which has two main functions: movement control and recognizing.…”
Section: Motion Controlmentioning
confidence: 99%
“…According to the previous studies [33][34][35], through the feedback of their own movement, visual observation or the feedback of avatar's (3D virtual character's) motion [36], humans can recognize and coordinate their movements better. The motion control module is the core of the system, which has two main functions: movement control and recognizing.…”
Section: Motion Controlmentioning
confidence: 99%
“…Motion control Recent research on neuroscience found that in human brain development there is a strong connection between perception, imagination and movement. According to previous studies [24][25][26], through the feedback of their own movement visual observation or the feedback of avatar's (3D virtual character's) motion [27], human can recognize and coordinate with their movements better.…”
Section: B Input Data Processingmentioning
confidence: 99%
“…There was cognitive disconnect in the relation of physical movements to DP results [13,15]. This eroded the concept of self in the DP, and would not translate well to a PUI.…”
Section: G Microphone Control -Phoneme Recognition Lip Synchmentioning
confidence: 99%
“…Hand and finger operation to perform these movements also required complex coordination [13,15], and therefore also served to distance the user from the DP.…”
Section: G Microphone Control -Phoneme Recognition Lip Synchmentioning
confidence: 99%